Antioxidants and Skeletal Muscle Performance: “Common Knowledge” vs. Experimental Evidence - Hernández, Andrés; Cheng, Arthur J.; Westerblad, Håkan (Frontiers in Physiology, 2012)
Antioxidants are assumed to provide numerous benefits, including better health, a reduced rate of aging, and improved exercise performance. Specifically, antioxidants are commonly ‘prescribed’ by the media, supplement industry, and ‘fitness experts’ for individuals prior to training and performance, with assumed benefits of improved fatigue resistance and recovery. This has provoked expansion of the supplement industry which responded by creation of a plethora of products aimed at facilitating the needs of the active individual. However, what does the experimental evidence say about the efficacy of antioxidants on skeletal muscle function? Are antioxidants actually as beneficial as the general populous believes? Or, could they in fact lead to deleterious effects on skeletal muscle function and performance? This mini review addresses these questions with an unbiased look at what we know about antioxidant effects on skeletal muscle, and what we still need to know before conclusions can be made.